2018
DOI: 10.21009/biosferjpb.11-1.1
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of comprehension reading skill and higher-order thinking skill with scientific literacy skill of senior high school biology teacher

Abstract: ABSTRAKPenelitian ini bertujuan untuk mengetahui hubungan antara kemampuan membaca pemahaman, kemampuan berpikir tingkat tinggi, dan usaha adaptasi pada kemajuan teknologi dengan kemampuan literasi sains guru biologi SMA. Subjek penelitian adalah guru biologi SMA di Kabupaten Bekasi, berjumlah 64 orang. Sampel diambil secara simple random sampling. Penelitian ini menggunakan metode deskriptif kuantitatif, dan uji hipotesisnya korelasi berganda dengan rumus Pearson Product Moment pada α=0,05. Hasil penelitian d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
(9 reference statements)
2
4
0
Order By: Relevance
“…The results of this study indicated that there was a correlation between critical thinking skill and motivation together with the scientific literacy. This was in line with several study results which postulated that scientific literacy can be positively related to higher order thinking skills and intelligence levels (Yuriza, Adisyahputra, & Sigit, 2018), reading comprehension skill (Susiati et al, 2018), and scientific process skill (Handayani, Adisyahputra, & Indrayanti, 2018).…”
Section: Resultssupporting
confidence: 92%
“…The results of this study indicated that there was a correlation between critical thinking skill and motivation together with the scientific literacy. This was in line with several study results which postulated that scientific literacy can be positively related to higher order thinking skills and intelligence levels (Yuriza, Adisyahputra, & Sigit, 2018), reading comprehension skill (Susiati et al, 2018), and scientific process skill (Handayani, Adisyahputra, & Indrayanti, 2018).…”
Section: Resultssupporting
confidence: 92%
“…One of the factors to increase the ability of understanding and scientific literacy is reading. Reading can increase students' insights and knowledge, thus students can integrate the literacy they read with the knowledge they already have (Susiati et al, 2018Ayu et al, 2018. The lack of scientific literacy in students is also influenced by the teacher's knowledge of scientific literacy.…”
Section: Resultsmentioning
confidence: 99%
“…The results of preliminary studies reveal that the ability of scientific literacy is influenced by higher-order thinking skills (Rahayuni, 2016;Cahyana et al, 2017;Susiati et al, 2018). The results of the study revealed that there was linearity between higher-order thinking skills and scientific literacy abilities.…”
Section: Introductionmentioning
confidence: 92%